2015
DOI: 10.1007/s10935-015-0383-6
|View full text |Cite
|
Sign up to set email alerts
|

HIV Testing Among Teens Attending Therapeutic Schools: Having a Personal Source of Information About HIV/AIDS Matters!

Abstract: Being informed and using positive coping strategies are associated with engaging in health-promoting behaviors. We assessed whether the type of information source about HIV (personal or impersonal) and coping strategies (optimism, avoidance, or emotion-focused) are associated with HIV testing among adolescents attending therapeutic schools. Participants were 417 adolescents, ages 13 to 19, who attended one of 20 therapeutic day schools for emotionally/behaviorally disordered youth in two U.S. cities (Providenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Berkley-Patton et al, 2012;Harris, 2010;Williams et al, 2014), the Black church has also been seen as a source of HIV stigma (Bird & Voisin, 2013;Derose et al, 2014). However, previous research has successfully used these approaches to engage Black youth (Bogart et al, 2015;Swenson et al, 2015). Faith-based communities have relatively untapped potential for recruiting Black sexual minority youth for HIV interventions (Hill & McNeely, 2013;Molock et al, 2008;Woodyard et al, 2000).…”
Section: Solutions For Recruiting Young Black Sexual Minority Menmentioning
confidence: 99%
“…Berkley-Patton et al, 2012;Harris, 2010;Williams et al, 2014), the Black church has also been seen as a source of HIV stigma (Bird & Voisin, 2013;Derose et al, 2014). However, previous research has successfully used these approaches to engage Black youth (Bogart et al, 2015;Swenson et al, 2015). Faith-based communities have relatively untapped potential for recruiting Black sexual minority youth for HIV interventions (Hill & McNeely, 2013;Molock et al, 2008;Woodyard et al, 2000).…”
Section: Solutions For Recruiting Young Black Sexual Minority Menmentioning
confidence: 99%
“…Because interactions within peer groups offer opportunities for individuals to exchange and evaluate information, learn social norms, develop behavioral skills, and influence each other’s attitudes and behavior [ 25 ], an HIV and STI prevention initiative that targets peer groups by leveraging adolescent girls’ preference for multiplayer gaming experiences has the potential to have benefits above and beyond an intervention designed for a single individual. Indeed, research suggests that peers often serve as a valuable source of information about HIV and as role models for prevention strategies such as condom use [ 26 ]. For instance, a community-based pilot study demonstrated a 72% increase in the number of individuals getting tested for HIV and STI when peers recruited others through their social network [ 27 ].…”
Section: Introductionmentioning
confidence: 99%